Patterns of antimicrobial resistance in a pediatric cardiac intensive care unit - Nelya Bissenova (National Scientific Medical Center, 2017)
Objective: to report the antibiotic resistance rate of most frequently pathogens in pediatric cardiac intensive care unit (PCICU) during a fve-year period. Methods. A prospective study was performed on 4228 clinical samples (bloodstream, wound samples, respiratory tract, tracheobronchial tree, and central venous catheter) from patients in PCICU during the period 2012-2016. Identifcation of isolates and antibiotic susceptibility testing were performed by Vitek 2 automated system. Results. The percentages of most frequently isolated microorganisms in our PCICU were as follows: Klebsiella pneumoniae 8.9%, Pseudomonas aeruginosa 7.5%, Staphylococcus aureus 6.9%, coagulase negative staphylococci 5.3%, and Candida sp. 3.4%. During study period there is tendency increasing the percentage of detection Ps.aeruginosa from 2.6% to 10.8% (p=0.018), K.pneumoniae from 2.6% to 10.5% (p=0.023), and Candida sp. from 1.6% to 5.9% (p=0.033). These isolates showed tendency of signifcant increasing resistance to 3rd generation cephalosporins and carbapenems. Conclusion. The present study reported that most frequent isolates in our PCICU were Ps.aeruginosa and K.pneumoniae. Reporting of dramatically increasing resistance rates of these isolates necessitates a well-designed hospital infection control strategy, including good hygiene, microbiological monitoring; all of this will greatly reduce the risk of nosocomial infection.